Fiscal Transparency for Sustainable Development: The Global Evidence - Jingyuan Xu; Xiaohu Wang; Hanyu Xiao; Zhihang Yuan (Public Administration and Development, 2026)
ABSTRACT Sustainable development (SD) has been a primary policy effort in government globally to address various key challenges in development and the environment. Transparency, as an accountability tool, is critical for stakeholders holding government administrations accountable for SD policy outcomes. Given the very limited literature on the role of administrative transparency in SD, this study creates a comprehensive global panel database covering the period from 2006 to 2022 to examine the effect of fiscal transparency on sustainability policy performance. The results indicate a significant role of developing transparency institutions in promoting SD goals, and distinctive effect of such development in countries of different development stages. The findings point to different paths for achieving accountability goals under different institutional conditions, which is significant for establishing and strengthening accountability enhancement strategies for policy outcomes.